Features of surface modification of copper-based alloys under powerful plasma exposures - Byrka, O.; Aksenov, N.; Chunadra, A.; Fomina, L.; Herashchenko, S.; Makhlai, V.; Malykhin, S.; Sereda, K.; Surovitskiy, S.; Garkusha, I. (Вопросы атомной науки и техники, 2018)
Paper presents features of plasma alloying of Cu-based materials with Ti-Cr, Ti-Cr-Ti-Nb, Ti-Cr-Ti-Zr, Ti-Cr-TiZrO coatings in different regimes of the QSPA Kh-50. Targets were made from copper samples covered of
multilayer PVD coatings have been deposited within a Bulat-type facility. Prepared targets were irradiated with
powerful plasma streams with energy loads achieved 0.6 MJ/m2
and the pulse duration of 0.25 ms. Influence of
plasma impacts on modification different copper alloys has been analyzed. Mechanisms of modification of thin
multilayered coatings mixed with Сu substrate in a liquid phase under the plasma processing are evaluated. Описано особливості плазмового легування матеріалів на основі міді з покриттями Ti-Cr, Ti-Cr-Ti-Nb, TiCr-Ti-Zr, Ti-Cr-Ti-ZrO в різних режимах КСПП Х-50. Проаналізовано вплив плазмових навантажень на
модифікацію різних мідних сплавів. Зразки було виготовлено з міді та багатошарових покриттів, які
утворювались PVD-методом в установці булатного типу. Підготовлені мішені опромінювалися потужними
плазмовими потоками з енергетичними навантаженнями, що досягали 0,6 МДж/м
2
, з тривалістю імпульсу
~ 0,25 мс. Обговорюються механізми модифікації тонких багатошарових покриттів, змішаних з мідною
підкладкою в рідкій фазі при плазмовому опроміненні. Описаны особенности плазменного легирования материалов на медной основе с покрытиями Ti-Cr, Ti-CrTi-Nb, Ti-Cr-Ti-Zr, Ti-Cr-Ti-ZrO в разных режимах КСПУ Х-50. Проанализировано влияние плазменных
нагрузок на модификацию разных медных сплавов. Образцы были изготовлены из меди и многослойных
покрытий, осажденных PVD-методом в установке булатного типа. Подготовленные мишени облучались
мощными плазменными потоками с энергетическими нагрузками, достигавшими 0,6 МДж/м2
, с
длительностью импульса ~ 0,25 мс. Обсуждаются механизмы модификации тонких многослойных
покрытий, смешанных с медной подложкой в жидкой фазе при плазменном облучении.